2016
DOI: 10.1002/cam4.750
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic potential of the MDM2 309T>G polymorphism in stage I lung adenocarcinoma

Abstract: The MDM 2 protein plays an important role in the regulation of cell proliferation and apoptosis via ubiquitination and proteasome‐mediated degradation of p53. The genetic polymorphism rs2279744 (c.309T>G) of the MDM 2 gene is reportedly associated with susceptibility and/or prognosis in various cancers. In this study, we investigated the risk factors for worse survival in patients with lung adenocarcinoma ( AC ). We examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Only one previous study took the p53 status into account, limited to stage I tumors, showing a better OS in wild type p53 patients harboring the SNP309TG or SNP309GG genotype 15 . Recently, Enokida et al reported similar results, showing that the SNP309TT genotype was predictive for poorer survival in stage I patients, without taking the p53 status into account 16 . These data seem inconsistent with our results in stage 1 tumors (data not shown).…”
Section: Discussionmentioning
confidence: 78%
“…Only one previous study took the p53 status into account, limited to stage I tumors, showing a better OS in wild type p53 patients harboring the SNP309TG or SNP309GG genotype 15 . Recently, Enokida et al reported similar results, showing that the SNP309TT genotype was predictive for poorer survival in stage I patients, without taking the p53 status into account 16 . These data seem inconsistent with our results in stage 1 tumors (data not shown).…”
Section: Discussionmentioning
confidence: 78%
“…There was, however, no effect of either polymorphism on age at diagnosis of LC or on overall survival [ 47 ]. Enokida et al published a case-control study showing gene MDM2 T/T, T/G, G/G polymorphic variants frequencies in samples to be 21.1%, 49.7%, and 30.2%, respectively [ 48 ]. Our study polymorphisms frequencies of MDM2 c.-5+309 G>T gene T/T, T/G, G/G showed that T/T polymorphic variant dominates and frequencies are 50.00%, 43.48%, 6.52%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…An Asian-Japanese study reported reduced overall survival of carriers of the MDM2 rs2279744 TT genotype as compared to carriers of the TG or GG genotypes (P=0.02) for patients with stage I lung adenocarcinoma (26). An Asian-Chinese study reported that carriers of MDM2 rs1690924 AG genotype were more sensitive to gastrointestinal toxicity than carriers of the wildtype homozygote GG [OR (95% CI) =2.32 (1.30-4.14), P=0.004)], suggesting MDM2 rs1690924 could be used to predict the toxicities of platinum-based chemotherapy in patients with advanced NSCLC (27).…”
Section: Discussionmentioning
confidence: 99%
“…Jar, data of TP53 from previous study (Yin et al submitted and revised); b , only list statistical significant models; C , balanced accuracy; d , cross-validation; e , P value based on 1,000 permutation test, statistical significant P value. 4784 chemotherapy outcome in lung cancer patients(26)(27)(28)(29).To the best of our knowledge, none of the remaining four htSNPs have been assessed previously in relation to lung cancer risk. The majority of the MDM2 SNP studies have…”
mentioning
confidence: 99%